The Effect of Red Binahong Extract (Andredera cordifolia (Ten.) Steenis) on Healing of Cesarean Section Surgical Wounds - Tien Tirta Nurulita; Jehani Fajar Pangestu; Dianna Dianna (MEDICA (International Medical Scientific Journal), 2025)
Cesarean section is an artificial delivery procedure involving an incision in the abdominal wall and uterus, which can cause pain at the suture site for up to six months. Binahong leaves are known to have properties that accelerate wound healing, both externally and internally. This study aims to determine the effect of binahong leaf extract on wound healing after cesarean section at the Sambas Regional General Hospital, Sambas Regency. This study used a quantitative method with a quasi-experimental design and a posttest nonequivalent control group design. Sampling was conducted using non-probability sampling with purposive sampling techniques, involving 34 respondents. The Shapiro-Wilk normality test showed that the data were not normally distributed (p<0.05), so the analysis was continued with the Mann Whitney non-parametric test. The test results showed a p-value of 0.000, which means that there was a significant difference between the intervention and control groups. Thus, the administration of binahong leaf extract had an effect on accelerating the healing of cesarean section wounds. The conclusion of this study is that binahong leaf extract significantly accelerates the average healing of post-cesarean section wounds at Sambas Regional General Hospital, making it a potential adjunct therapy in post-surgical care.